A new stalagmite oxygen isotope record over the last 1350 years: Insights into spatial variation in Asian summer monsoon and temperature forcing. (15th May 2022) - Duan, Fucai; Zhang, Zhenqiu; Liu, Dianbing; Shao, Qingfeng; Zhao, Kan; Wang, Yongjin
Abstract: Climate reconstructions over the last millennium are essential to estimate natural and anthropogenic forcing. Here we present a stalagmite δ 18 O record from southwestern China, which characterizes changes in the Asian Summer Monsoon (ASM) precipitation over the past 1350 years. Wet climate is clearly identified during the Dark Age Cold Period (DACP) and Little Ice Age (LIA); dry climate is clearly identified during the Medieval Warm Period (MWP) and Current Warm Period (CWP). These precipitation oscillations, except that over the CWP, are remarkably similar to, but strongly antiphase with, those in northwestern China. Over the CWP, our δ 18 O record, similar to other stalagmite records in East Asia, also exhibits a gradually increasing trend. This trend has been assumed to be caused by anthropogenic temperature warming. Here a better correlation is identified between our record and atmospheric temperature change during the preindustrial and industrial eras. This correlation provides solid evidence for the consistent modulation of the temperature on the ASM precipitation without and with the human-induced forcing. However, this modulation may act in a different manner during the industrial era, which results in the same δ 18 O variation across East Asia. In sum, our record provides a clear spatial variation of the ASM precipitation and highlights persistent temperature modulation on the ASM without and with anthropogenic emissions. Highlights: A new stalagmite record clearly shows a wet DACP and LIA, but dry MWP and CWP in southern China. Precipitation variations in southern China are antiphase with those in northern China on the multi-centennial scale. Precipitation in southern China changed in step with atmospheric temperature throughout the last millennium.